Mary Coin - Silver, Marisa (New York : Blue Rider Press, 2013)
In 1936, a young mother resting by the side of a road in central California is spontaneously photographed by a woman documenting the migrant laborers who have taken to America's farms in search of work. Little personal information is exchanged, and neither woman has any way of knowing that they have produced what will become the most iconic image of the Great Depression. - from cover p.[2]
Keywords: Women migrant labor -- Fiction; Women photographers -- Fiction; Depressions -- 1929 -- Fiction; Photojournalism -- United States -- History -- 20th century -- Fiction; Rural poor -- United States -- Fiction